Strategi Orientasi Pasar Dalam Menciptakan Keunggulan Bersaing - Ruhiyantina, Nurrisbayanti; Wibowo, Lili Adi; Widjajanta, Bambang (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2017)
This research was conducted to see how much influence market orientation has on competitive advantage. This type of research is descriptive and verification with samples taken as many as 20 respondents who meet the criteria set out in the study. The data analysis technique in this study uses simple regression. Based on the results of the study using simple regression analysis, the results show that market orientation has a significant effect on competitive advantage. The difference between this research and other research lies in the object of research, the measurement instrument used, the population and the sample of the study, and the results of the research. In this study using theories from journals and books, so the theory used is different.